Deoxyribonucleic Acid Based Nonce-Misuse-Resistant Authenticated Encryption Algorithm - Akumalla, Harichandana; Hegde, Ganapathi (International Conference on Electronics, Materials Engineering and Nano-Technology (Online), 2021)
This paper aims to present a performance comparison of new authenticated encryption (AE) algorithm with the objective of high network security and better efficiency as compared to the defacto standard. This algorithm is based on a critical property of nonce-misuse-resistance incorporating DNA computation for securing the key, here the processing unit of DNA block converts the input key into its equivalent DNA base formats based on the ASCII code table. The need for secure exchange of keys through a public channel has become inevitable and thus, the proposed architecture will enhance the secrecy by using DNA cryptography. These implementations consider Advanced Encryption Standard in Galois Counter mode (AES-GCM) as a standard for comparison.